Dampak Motivasi Usaha Terhadap Kinerja Usaha Pada Industri Kulit Sukaregang Kabupaten Garut - Trustorini Handayani; Sabila Nurjamilah (Pusat Riset dan Inovasi Nasional, 2022)
There has been a lot of rapid growth in Micro, Small and Medium-sized Enterprises (MSMEs) in Indonesia in recent years. MSMEs are critical to the overall health of the national economy. They are responsible for creating jobs and generating profits, which in turn helps support other parts of the economy. The development of MSMEs is hoped to reduce the unemployment rate, which will result in an increase in people's purchasing power and growth in the country's economy. The purpose of the study is to see an overview of how business motivation and performance and the impact of business motivation on the performance of business actors. The population is 461 business actors. The sampling technique using the Slovin Formula was obtained by a sample of 81 people. The analysis method in this study uses descriptive and verificatif analysis consisting of regression analysis, correlation, coefficient of determination. The results of the descriptive analysis show that business motivation has a score of 81.36 which means that business actors have excellent business motivation with the lowest score on the expectation indicator and the highest score on the intensive indicator. As for the Business Performance variable, it has a score of 69.52 which means that business actors already have good business performance with the lowest score on the indicator of increasing sales and the highest score on the indicator of increasing profits. The results of the verificative analysis Business motivation has a significant effect on business performance in the Sukaregang Kulit Industry Center, Garut Regency. Good business motivation is needed to support business performance.